Penggunaan Boraks Sebagai Bahan Pengawet Substrat Serat Aren untuk Hidroponik Tomat - Rena Satya Tungga Dewi; Dwi Harjoko; Retna Bandriyati Arniputri (Agrosains : Jurnal Penelitian Agronomi, 2020)
Palm fiber from palm flour industries waste often causes problems when used as a planting medium such as easy to decompose. The plants used are tomatoes, because of their low production due to the use of fertilizers and planting media that are not yet right. One of the cultivation techniques that is expected to improve yields and quality of tomatoes is hydroponics. The research aimed to knowing the effect of borax on palm fiber decomposition after it is used for tomato cultivation. The research was carried out at Greenhouse B Faculty of Agriculture, Universitas Sebelas Maret, Surakarta from January-July 2019. The method used was Completely Randomized Factorial Design with 2 factors and 3 replications. The first factor was the soaking time of the palm fiber substrate in the borax solution 10% of concentration, which is 0, 1, 2, 3 and 4 days. The second factor was the variety of tomato varieties, namely Servo and Ken Dedes. The results showed that soaking treatment not significantly affected to almost all observed variables and tomato varieties not significantly affected to the growth and yield.